Variation in seed morpho-physiological and biochemical traits of Java olive populations originated from Java, Bali, Lombok, and Timor Islands, Indonesia - DEDE J. SUDRAJAT; ICHSAN SUWANDHI; ISKANDAR Z. SIREGAR; ULFAH J. SIREGAR (Biodiversitas Journal of Biological Diversity, 2018)
Sudrajat DJ, Suwandhi I, Siregar IZ, Siregar UJ. 2018. Variation in seed morpho-physiological and biochemical traits of Java olive populations originated from Java, Bali, Lombok, and Timor Islands, Indonesia. Biodiversitas 19: 1004-1012. Java olive (Sterculia foetida L.) is one of the promising non-edible feedstocks for biodiesel production. Utilization of this tree species for plantation is limited due to knowledge gaps in many fundamental aspects of seed properties. The aim of the study was to determine the variation that may exist among java olive seed collected from Bogor, Palimanan, Tuban, Gilimanuk, Pemenang and Naioni populations, and to analyze correlations between one or many seed morpho-physiological and biochemical traits. Analysis of variance showed significant differences of seed morphological and biochemical traits, except for the germination capacity. Seed morphological traits were not significantly correlated with agro-climate factors, while some of biochemical traits revealed significant correlation with some agro-climate factors. Genotypic variance and genotypic coefficient of variation were higher for fruit length, fruit width, carbohydrate, fat, protein and oil contents, indicating higher genetic contribution on the variance of these traits. High heritability values combined with high genetic gain was found for protein content, fruit width and oil content, that revealed the characters having highly genetic origin with a good number of heritable components. Population clustering exhibited that most of the geographically distant population are genetically related. Pemenang population was found highly associated with oil content, indicating that the population have high potency to develop as the feedstocks for for biodiesel production.